2019
DOI: 10.1259/bjr.20180464
|View full text |Cite
|
Sign up to set email alerts
|

The MRI characteristics of non-mass enhancement lesions of the breast: associations with malignancy

Abstract: The breast imaging-reporting and data system (BI-RADS) was first published in 2003 by the American College of Radiology (ACR) with an aim to standardize the interpretation and reporting of breast imaging. 1 Apart from standardization, the BI-RADS lexicon may be used as a tool to distinguish between benign and malignant lesions and resolve uncertainties in tumor identification. 2,3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
3
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 30 publications
9
40
3
7
Order By: Relevance
“…Nevertheless, for the lesion with clustered ring enhancement, in addition to the risk of DCIS and invasive breast cancer, benign lesions such as complex sclerosis, papilloma and fibrocystic disease should also be taken into account [32]. The positive predictive value of clustered ring enhancement for malignancy varied greatly with the range of 41.9-100% due to the different patient populations between studies [30,[32][33][34]. The clustered enhanced ring used in the current study was referred to as multiple rings clustered together regardless of ring size, including the aforementioned clustered ring enhancement and larger rings clustered together which was not included in the 5th BI-RADS MRI lexicon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, for the lesion with clustered ring enhancement, in addition to the risk of DCIS and invasive breast cancer, benign lesions such as complex sclerosis, papilloma and fibrocystic disease should also be taken into account [32]. The positive predictive value of clustered ring enhancement for malignancy varied greatly with the range of 41.9-100% due to the different patient populations between studies [30,[32][33][34]. The clustered enhanced ring used in the current study was referred to as multiple rings clustered together regardless of ring size, including the aforementioned clustered ring enhancement and larger rings clustered together which was not included in the 5th BI-RADS MRI lexicon.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses showed that segmental distribution had the highest odds ratios of 4.739 and 5.1 for discriminating benign and malignant NME lesions [30, 31]. The positive predictive value for malignancy of segmental distribution ranged from 67 to 100% [34]. In the 5th edition lexicon, ductal distribution has been changed to the term “linear.” Linear distribution is divided into two patterns: single line or branching.…”
Section: Discussionmentioning
confidence: 99%
“…Aydin reviewed 129 NME lesions retrospectively aiming to differentiate between the benign versus malignant lesions [ 6 ]. He found that the segmental and diffuse distribution as well as clustered-ring internal enhancement was linked to malignancy; on the other hand, the linear distribution as well as homogeneous enhancement types were associated with benignity.…”
Section: Reviewmentioning
confidence: 99%
“…Some of these areas are identified as malignant, including IDC, ductal carcinoma in situ (DCIS) and tubular carcinoma. Others are diagnosed as benign masses, such as sclerosing adenosis, atypical ductal hyperplasia, fibroadenoma and mastitis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…4).Das gruppierte und ringförmig gruppierte Muster des inneren Enhancements ist laut Studienergebnissen als suspekt zu werten (▶ Abb. 5)[9,10].…”
unclassified